The Play's the Thing: Associations between Make-Believe Play and Self-Regulation in the Tools of the Mind Early Childhood Curriculum. Issue 1 (2nd January 2020) - Baron, Alex; Malmberg, Lars-Erik; Evangelou, Maria; Nesbitt, Kimberly; Farran, Dale
ABSTRACT: Make-believe play has been theorized to promote self-regulation skills and other positive child outcomes. In this study, we examine the make-believe play approach featured in the Tools of the Mind (Tools) early childhood curriculum, which identifies students' self-regulation cultivation among its core programmatic aims. Using data from 42 classrooms in the United States, we specified latent growth models to investigate the association between Tools make-believe play and children's self-regulation development throughout pre-kindergarten, kindergarten, and first grade ( N = 646 students aged between four and seven years old). We found that higher implementation frequency and fidelity of Tools play predicted less self-regulation growth. Implications for policy and practice are discussed.